2017
DOI: 10.1038/s41598-017-02731-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for reducing the fertilizer application rate in the ridge and furrow rainfall harvesting system in semiarid regions

Abstract: The ridge and furrow rainwater harvesting (RFRH) system is a promising water-saving planting technique for dryland farming, but we lack a full understanding of the effects of different fertilizer rates (N:P) on plant nutrient uptake and nutrient use efficiency (NuUE) in foxtail millet using this planting method, as well as the available nutrient residues in the soil. We conducted field studies (Loess Plateau, China) comparing RFRH planting (R) and traditional flat planting (T) at four different fertilizer rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Past researchers reported that there is positive and significant relationship between irrigation water use and intensity of fertilizer application (Yan et al, 2019;Zafar et. al., 2020;Feng et al, 2020;Lian et al, 2017). Similar results were also observed in the study area.…”
Section: Fertilizer Applicationsupporting
confidence: 88%
“…Past researchers reported that there is positive and significant relationship between irrigation water use and intensity of fertilizer application (Yan et al, 2019;Zafar et. al., 2020;Feng et al, 2020;Lian et al, 2017). Similar results were also observed in the study area.…”
Section: Fertilizer Applicationsupporting
confidence: 88%
“…suggests that low N absorption, which reduces gs and inhibits carbon assimilation, could affect leaf expansion and photosynthesis because water and N are the main factors controlling plant growth. WUEi was significantly higher in organic farming, as stated in previous studies 59,60 . The results of chlorophyll content and protein concentration did not show differences, despite the fact that a low N supply to the soil has been associated with the degradation of chlorophyll molecules, 61 and an increase in N fertilizers has been linked to an increase in protein concentration 62 …”
Section: Discussionsupporting
confidence: 73%
“…Results corroborate with findings by Mupangwa et al (2012) and (Nyakudya et al (2014) who found moisture benefits at access tubes placed closer to the rainwater harvesting technique while those further away had little moisture benefits which result in differential plant growth. Moisture gradients created as distance increase results in differential moisture interception and uptake for plant development and hence yield (Lian et al, 2017;Mhizha and Ndiritu, 2013;Mupangwa et al, 2012).…”
Section: Grain Yieldmentioning
confidence: 99%
“…Higher sorghum grain yield in nitrogen applied treatment compared with no nitrogen applied treatments in the RWH methods (Figure 7) explains the importance of nitrogen in crop growth. Water and nitrogen availability are important in the production of photoassimilates and partitioning at the economic sink for the production of grain (Lian et al, 2017).…”
Section: Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation